Acute changes in electrophysiological brain dynamics in elite karate players - Duru, A. D.; Balcioglu, T. H.; Özcan, C. E.; Dilek, C.; Duru, G. (Iranian Journal of Science and Technology, Transactions of Electrical Engineering, 2020)
Regular physical exercise has enhanced effects on the human anatomy and functionality. Recently, an effect of a single set of exercise is shown to have positive effects on mood and on cognitive functioning. The aim of this study is to investigate the effect of a single bout of moderate exercise on the brain electrophysiological dynamics in resting-state condition and under the mental workload situation from elite-level athletes. For this purpose, electroencephalogram (EEG) is measured before and after the exercise sessions from 17 elite karate players who are members of the national karate team of Turkey. Blood lactate measurements are implemented to monitor the volunteers before EEG measurements. EEG data are analyzed using three metrics: conventional band power of each electrode, coherence metrics between electrodes for each band and source coherence values corresponding to each frequency band. Each metric is statistically analyzed between pre- and post-values, and results revealed that in all frequency bands, right parietal electrode had increased connection values which are thought to be related to ongoing sympathetic nervous system response observed during the recovery period. Another finding is the enhanced connectivity of frontal sources under the resting state as well as during the increased mental workload periods.